DIAGNOSIS OF CHILDHOOD NON-HODGKIN LYMPHOMA - Adriana Sărsan; Constantin Arion (Amaltea Medical Publishing House, 2008)
In children, non-Hodgkin lymphoma manifests as a heterogeneous group of tumors. The clinical presentation correlates strongly with the tumor's immunophenotype and histologic features. When a child is suspected of having non-Hodgkin lymphoma, the evaluation needs to proceed speedily and systematically. Immunophenotypic and cytogenetic studies will help identify the lineage and progeny of the tumor. Molecular diagnostic techniques are increasingly being used to aid în diagnosis. Imaging studies are essential to document the extent of disease involvement and they should not delay the onset of chemotherapy, as childhood non-Hodgkin lymphoma is one of the most rapidly proliferating tumor types în humans. PET scans have been useful în detecting metabolic activity în otherwise occult sites of tumor involvement. The most widely used staging system is the system reported by St.Jude Children's Research Hospital, with therapeutic and prognostic implications.